< 50-μm thin crystalline silicon heterojunction solar cells with dopant-free carrier-selective contacts. (October 2019) - Dai, Hao; Yang, Liu; He, Sailing
Abstract: Dopant-free carrier-selective contacts are emerging in the field of crystalline silicon (c-Si) photovoltaic solar cells, which are potential to further improve the power conversion efficiency (PCE) and lower the cost of c-Si solar cells. Here, we demonstrate tens of microns thin c-Si heterojunction solar cells with substochiometric MoOx and LiFx as dopant-free hole- and electron-selective contacts, respectively. Chemical thinning of 200-μm thick c-Si wafers enables the production of proof of concept devices with good flexibility and strong performance. When the wafer thickness is reduced to 49.4 μm (24.7% of the initial thickness), the power conversion efficiency (PCE) of the solar cell still maintains 88.2% of the initial value for the 200-μm thick cell. When the wafer thickness becomes less than 10% (or even 3.4%) of the initial value, 61.2% and 39.2% of the initial PCEs are still achieved for the 14.8- and 6.8-μm thick cells, respectively. Passivating and carrier-selective effects of the MoOx and LiFx films allow for the maintenance of performance. An oxide interlayer at the MoOx /c-Si interface passivates the dangling bonds of the c-Si surface and improves the minority carrier lifetime. Field-effect passivation and carrier-selective effects induced by the band bending near the MoOx /c-Si interface and the Al/LiFx /c-Si interface play an important role in maintaining high open-circuit voltage and high fill factor. To the best of our knowledge, this is the first time that <100-μm thin c-Si heterojunction solar cells are reported with undoped contacts. Our solar cells have been fabricated on thin c-Si wafers with low-temperature processes and without additional doping, and thus our work provides a promising cost-effective means in the field of thin and flexible c-Si solar cells. Graphical abstract: Image 1 Highlights: Thin c-Si solar cells with undoped contacts are demonstrated for the first time. Good power conversion performances are achieved for thin c-Si solar cells. Passivating and carrier-selective effects of the undoped contacts are studied.